Report on the conference ”The humanities for business. Man in the world of ideas” - Kasprzyk, Damian (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2012)
Report on the conference ”The humanities for business. Man in the world of ideas”.